2004
DOI: 10.1128/mcb.24.10.4092-4103.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Two Steps of Poly(A)-Dependent Termination, Pausing and Release, Can Be Uncoupled by Truncation of the RNA Polymerase II Carboxyl-Terminal Repeat Domain

Abstract: The carboxyl-terminal repeat domain (CTD) of RNA polymerase II is thought to help coordinate events during RNA metabolism. The mammalian CTD consists of 52 imperfectly repeated heptads followed by 10 additional residues at the C terminus. The CTD is required for cleavage and polyadenylation in vitro. We studied poly(A)-dependent termination in vivo using CTD truncation mutants. Poly(A)-dependent termination occurs in two steps, pause and release. We found that the CTD is required for release, the first 25 hept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 64 publications
(124 reference statements)
1
44
0
Order By: Relevance
“…After misincorporation, the mismatched nucleotide at position +1 of the RNA is frayed away from the template, thereby pausing RNAP. Pausing is the first step in backtracking [63,[76][77][78][79][80][81][82][83]. The frayed nucleotide then inhibits RNA extension, because it prevents NTP binding, but favors backtracking, because the bp in position +1 is disrupted.…”
Section: Model For Transcriptional Proofreadingmentioning
confidence: 99%
“…After misincorporation, the mismatched nucleotide at position +1 of the RNA is frayed away from the template, thereby pausing RNAP. Pausing is the first step in backtracking [63,[76][77][78][79][80][81][82][83]. The frayed nucleotide then inhibits RNA extension, because it prevents NTP binding, but favors backtracking, because the bp in position +1 is disrupted.…”
Section: Model For Transcriptional Proofreadingmentioning
confidence: 99%
“…It has been suggested that the poly(A) signal itself can direct RNAPII pausing. The AAUAAA-dependent pausing is mediated by CPSF but does not require the CTD and any other downstream pausing elements (Orozco et al 2002;Park et al 2004;Nag et al 2006Nag et al , 2007. Another sequence, a CCAAT-box in the adenovirus late promoter is necessary for termination of the upstream gene (Connelly and Manley 1989).…”
Section: Pausing the Polymerase: Another Factor In Rnapii Terminationmentioning
confidence: 99%
“…Interestingly, Pcf11 transcript release activity requires a paused polymerase (Zhang et al 2005;Zhang and Gilmour 2006). Therefore, it is possible that the intrinsic ability of the poly(A) signal to pause the polymerase (Orozco et al 2002;Park et al 2004) is related to activation of the Pcf11 transcript release activity.…”
Section: Introductionmentioning
confidence: 99%